2021
DOI: 10.1002/hed.26712
|View full text |Cite
|
Sign up to set email alerts
|

CD15+ tumor infiltrating granulocytic cells can predict recurrence and their depletion is accompanied by good responses to S‐1 with oral cancer

Abstract: BackgroundIt has been reported in oral squamous cell carcinoma (OSCC) that myeloid‐derived suppressor cells infiltrate tumor tissues. This study examined whether S‐1 chemotherapy changes immune cell populations in the tumor microenvironment.MethodsWe examined 71 patients with of OSCC, including 51 patients who received preoperative S‐1 chemotherapy. Immunohistochemistry for PD‐L1, CD8, forkhead box protein 3 (FOXP3), and CD15 was performed using biopsy and resected specimens.ResultsThe numbers of CD8+, FOXP3+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…CD15+ MDSC is present in the tissue of oral cancer. Immunohistochemistry analysis of biopsy and resected specimens proved that decreasing its number due to preoperative chemotherapy can improve the prognosis [94].…”
Section: Experimental Medicine Involving Cd15mentioning
confidence: 99%
“…CD15+ MDSC is present in the tissue of oral cancer. Immunohistochemistry analysis of biopsy and resected specimens proved that decreasing its number due to preoperative chemotherapy can improve the prognosis [94].…”
Section: Experimental Medicine Involving Cd15mentioning
confidence: 99%
“…Overall, the studies report on a total of 920 patients (range 21–161), with studies coming from Europe ( n = 6, 40%) [ 30 , 31 , 32 , 33 , 34 , 35 ], China ( n = 3, 20%) [ 36 , 37 , 38 ], Japan ( n = 3, 20%) [ 39 , 40 , 41 ], Korea ( n = 2, 13%) [ 42 , 43 ], and the USA ( n = 1, 7%) [ 44 ]. The studies were published in the time range 2017–2021, with the vast majority appearing in the years 2020 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The study of So et al reported on the effect of radiotherapy, even though there was a minor quota of patients also treated with chemotherapy, and showed a decrease in PD-L1 expression in 69% of cases, with negativization in 23% [ 43 ]. In one study, the effect of a precursor of fluorouracil alone was investigated and the authors reported a significant decrease in PD-L1 expression in tumor cells [ 41 ], while the other studies where fluorouracil was deployed reported, on the contrary, an increase in the quota of positive cases [ 34 , 42 ]. In these studies, however, fluorouracil was used in combination with a platinum agent and docetaxel, and results were not stratified for different combinations of chemotherapy or cisplatin-based therapy separately.…”
Section: Discussionmentioning
confidence: 99%
“…CD15 + MDSCs are present in oral cancer tissues. Immunohistochemistry analysis of biopsy and resected specimens proved that decreasing their numbers with preoperative chemotherapy can improve prognoses [33]. Several factors regulate the functioning of MDSCs.…”
Section: Role Of Cd15 and Cd15s In Neoplasmsmentioning
confidence: 99%